NMR Spectroscopy of supramolecular chemistry on protein surfaces - Bayer, Peter; Matena, Anja; Beuck, Christine (Beilstein Journal of Organic Chemistry, 2020)
As one of the few analytical methods that offer atomic resolution, NMR spectroscopy is a valuable tool to study the interaction of proteins with their interaction partners, both biomolecules and synthetic ligands. In recent years, the focus in chemistry has kept expanding from targeting small binding pockets in proteins to recognizing patches on protein surfaces, mostly via supramolecular chemistry, with the goal to modulate protein–protein interactions. Here we present NMR methods that have been applied to characterize these molecular interactions and discuss the challenges of this endeavor.
Keywords: molecular recognition; NMR; protein ligand interaction; protein surfaces; supramolecular chemistry